2018
DOI: 10.1111/1754-9485.12819
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy patterns of care for stage I and II non‐small cell lung cancer in Sydney, Australia

Abstract: Introduction: Curative radiotherapy is guideline treatment for inoperable patients of good performance status with Stage I & II Non-Small Cell Lung Cancer (NSCLC). The aim of this study was to evaluate radiotherapy patterns of care in these patients, the reasons for palliative treatment and the proportion of patients suitable for curative stereotactic ablative body radiotherapy (SABR). Methods: Electronic oncology databases at three institutions were queried to retrieve data on patients with inoperable Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…A significant proportion of patients received curative intent radiotherapy due to medical inoperability or patient decision. The survival outcomes in our study were similar to previously published reports [17,[28][29][30], although inferior to surgery with 5-year OS being 26%. In both a multivariate model and a case-matched analysis, the performance of surgery remained superior to curative intent radiotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A significant proportion of patients received curative intent radiotherapy due to medical inoperability or patient decision. The survival outcomes in our study were similar to previously published reports [17,[28][29][30], although inferior to surgery with 5-year OS being 26%. In both a multivariate model and a case-matched analysis, the performance of surgery remained superior to curative intent radiotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Guidelines for locally advanced NSCLC suggest that a dose of 60 Gy should be used when treating with definitive radiotherapy, but it is not clear if this can be extrapolated to stage II disease [34]. Prior retrospective studies have defined curative radiotherapy for early stage NSCLC as a minimum dose of 50Gy [29,30]. Our study showed superior outcomes in patients treated with > 60 Gy compared to those treated with lower doses of potentially curative radiotherapy, which is consistent with other retrospective studies [17].…”
Section: Discussionsupporting
confidence: 78%
“…Studies from the Netherlands and Australia comparing the periods before and after the clinical introduction of SBRT, showed a shift from palliative radiotherapy/best supportive care to curative radiotherapy [12,15,18]. Our study included the period after the implementation of RT: radiotherapy; OR: odds ratio; CI: confidence interval; p25: 25th percentile; p75: 75th percentile; values in bold are statistically significant.…”
Section: Stage I and Iimentioning
confidence: 99%
“…Around 2010, SBRT was included in international guidelines as an alternative treatment option for inoperable patients with peripheral tumors, but not for those who are considered operable [4][5][6][7][8][9]. On the other hand, several authors have reported an increasing use of SBRT in early-stage NSCLC, both in operable patients instead of surgery [17] and in patients who previously would have received best supportive care alone [12,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Practice pattern studies have revealed wide variations in radiotherapy utilisation across different populations as well as service providers [10] , [11] , [12] , [13] , [14] , [15] , highlighting the need for establishing valid benchmarks of optimal utilisation rates that reflect actual demands within the population. Evidence-based models have previously been used to determine optimal utilisation rates for different radiotherapy and chemotherapy treatments [3] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%